The Measurement of Heparin and Other Therapeutic Sufphated Polysaccharides in Plasma, Serum and Urine - Dawes, J; Prowse, C V; Pepper, D D (Thrombosis and Haemostasis, 1985)
The competitive binding assay described will specifically and accurately measure concentrations of administered heparin in biological fluids with a sensitivity of 60 ng ml-1. Neither endogenous glycosaminoglycans, nor plasma proteins such as ATIII and PF4 interfere in the assay. Semi-synthetic highly sulphated heparinoids and LMW heparin can also be measured. Using this assay heparin clearance followed simple first-order kinetics over the dose range 100-5,000 units, but the half-life was strongly dose-dependent. There was good correlation with heparin activity measurements by APTT and anti-Xa clotting assays. Plasma concentrations were measurable for at least 5 h following subcutaneous injection of 10,000 units of heparin. Excretion in the urine could be followed after all but the lowest intravenous dose. This assay, used in conjunction with measurements of heparin anticoagulant activity, will be valuable in the elucidation of mechanisms of action of heparin and the heparinoids, and in the assessment and management of problems related to heparin therapy.
Keywords: Heparin; Heparinoids; Competitive binding assay; Clearance; Volunteer studies